ECONOMIC ANALYSIS OF OIL PALM PROCESSING IN OLA OLUWA LOCAL GOVERNMENT AREA, OSUN STATE, NIGERIA - Kaothar Modupe IDRIS-ADENIYI; Ahmed Olugbenga BUSARI; Afusat Adunni ALABI; Khadijat Olaitan OLANREWAJU; Munir Karounwi Adegoke WAHAB; Sekinat IGE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study investigated the profitability of oil palm processing venture in Ola Oluwa Local Government Area of Osun State, Nigeria. The sampled 120 respondents for the study were selected using a multistage sampling procedure. Field surveys were carried out using structured interview schedule to obtain primary data utilized for the study. Data analysis was carried out using frequencies, percentages, means, and regression analysis. Results of the descriptive analysis revealed that the majority of the respondents were middle-aged (mean = 58.43 years) (92.5%), married (55.83%), female (100%), having a mean of the household size of 5 persons per household. The majority (60.00%) of the respondents had no formal education; do not own an oil palm processing unit (77.31%); small-scale processors (44.54%), with a mean of 37.21 litres of palm oil per production cycle. The mean years of oil palm processing experience, total revenue, total production cost, gross margin, and net income from oil palm processing per year were 28.39 years, ₦243,472.900, ₦103,088.808, ₦155,521.592 and ₦140,384.092 respectively. Regression results revealed that the cost of oil palm bunches, the cost of firewood, the cost of kerosene, and matches, and the cost grinding were positive significant determinants of the level of gross margin from oil palm processing in the study area. Based on the findings, the study concluded that despite the profitability oil palm processing venture in the study area, it is operated on a small-scale predominantly by aged married and widowed women; hence provision of financial assistance through low-interest loans from agricultural banks or any other related financial institution would help improve their productivity.